The house next door [compact disc, unabridged] : thrillers - Patterson, James, 1947-; DiLallo, Susan, 1947-; DiLallo, Max; Arnold, Tim, (Journalist) (Hachette Audio, 2018)
At first, Laura Sherman is thrilled to meet a fresh face, but will her relationship with the man next door go too far before she realizes he's not what he seems? Detective Andrew McGrath knows the only way to find six girls that have vanished without a trace is to get close to the suspect's wife - but will he get too close? Robert Barnett, a disgraced scientist, receives a shocking message that could change the world. But when a nationwide manhunt has him on the run for his life, will his dream discovery turn into a nightmare?